Associations of Lipoprotein(a) With Coronary Atherosclerotic Burden and All-Cause Mortality in Patients With ST-Segment Elevation Myocardial Infarction Treated With Primary Percutaneous Coronary Intervention - Xue, Yuzhou; Jian, Shen; Zhou, Wei; Zhou, Qi; Xiang, Jing; Zhu, Yuansong; Xiang, Zhenxian; Yang, Haonan; Liu, Gang; Luo, Suxin (Frontiers in cardiovascular medicine, 2021)
Background: The coronary atherosclerotic burden in patients with ST-segment elevation myocardial infarction (STEMI) has been identified as the main predictor of prognosis. However, the association of lipoprotein(a) [Lp(a)], a well-established proatherogenic factor, with atherosclerotic burden in patients with STEMI is unclear. Methods: In total, 1,359 patients who underwent percutaneous coronary intervention (PCI) for STEMI were included in analyses. Three prespecified models with adjustment for demographic parameters and risk factors were evaluated. Generalized additive models and restricted cubic spline analyses were used to assess the relationships of Lp(a) with Gensini scores and the no-reflow phenomenon. Kaplan–Meier curves were generated to explore the predictive value of Lp(a) for long-term all-cause mortality. Furthermore, mRNA expression levels of LPA in different groups were compared using the GEO database. Results: Patients in the highest tertile according to Lp(a) levels had an increased incidence of heart failure during hospitalization. Furthermore, patients with high levels of Lp(a) (>19.1 mg/dL) had sharply increased risks for a higher Gensini score ( P for trend = 0.03) and no-reflow ( P for trend = 0.002) after adjustment for demographic parameters and risk factors. During a median follow-up of 930 days, 132 deaths (9.95%) were registered. Patients with high levels of Lp(a) (>19.1 mg/dL) had the worst long-term prognosis ( P for trend < 0.0001). In a subgroup analysis, patients with higher Lp(a) still had the highest all-cause mortality. Additionally, the mRNA expression levels of LPA in patients with STEMI with lower cardiac function were higher than those in other groups ( P = 0.003). A higher coronary atherosclerotic burden was correlated with higher LPA expression ( P = 0.01). Conclusion: This study provides the first evidence that Lp(a) (at both the protein and mRNA levels) is independently associated with coronary atherosclerotic lesions and prognosis in patients with STEMI treated with PCI. Clinical Trial Registration: http://www.chictr.org.cn/index.aspx , identifier: ChiCTR1900028516.